2006
DOI: 10.1111/j.1365-2265.2006.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and catecholamine response to sympathetic stimulation in turner syndrome

Abstract: Turner syndrome is associated with dysregulation of the sympathetic nervous system (SNS), leading to tachycardia and high BP, increased resting norepinephrine levels, and a greater tolerance of the cathecholamine response to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…These may be related to sympathetic dysregulation. TS patients are associated with increased resting norepinephrine levels and a compromised response to sympathetic stimulation: they have a sympathetic tolerance for physical stress and an inertia for sympathetic stimulation (86).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…These may be related to sympathetic dysregulation. TS patients are associated with increased resting norepinephrine levels and a compromised response to sympathetic stimulation: they have a sympathetic tolerance for physical stress and an inertia for sympathetic stimulation (86).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Nevertheless, given the possible b hypersensitivity and increased sympathetic tone found in TS patients, these drugs should be initiated with caution and in smaller than usual dosage. Treatment targeting the overactive SNS may be useful to prevent later cardiovascular complications in these patients (86).…”
Section: Cardiovascular Abnormalities In Transitionmentioning
confidence: 99%
“…This observation, together with the frequent elevations in systemic BP has led to the hypothesis of altered autonomic nervous system (ANS) activity in this disorder. One study documented a relatively higher heart rate and systolic BP in young women with TS compared to age-matched controls, and a higher level of resting norepinephrine in TS [37]. This study also found a compromised response to sympathetic stimulation in the TS group, and concluded that there is a deregulation of the sympathetic nervous system in TS [37].…”
Section: Abnormalities Of Cardiac Rate Conduction and Repolarizationmentioning
confidence: 84%
“…One study documented a relatively higher heart rate and systolic BP in young women with TS compared to age-matched controls, and a higher level of resting norepinephrine in TS [37]. This study also found a compromised response to sympathetic stimulation in the TS group, and concluded that there is a deregulation of the sympathetic nervous system in TS [37]. Another small study investigated heart rate variability in young adults with TS and reported relatively diminished low frequency power and concluded that there is decreased sympathovagal balance in TS [38].…”
Section: Abnormalities Of Cardiac Rate Conduction and Repolarizationmentioning
confidence: 96%
“…The contribution of both RAA axis and SNS in the pathogenesis of hypertension remains uncertain. SNS is rather over-activated in TS women [16]. Hormone therapy in TS patients is not only a treatment for short stature (growth hormone) and the compensation for sex hormone deficit (sex hormones), but also the counteraction to the deficit www.ah.viamedica.pl effects, including the reduction in the risk of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%